Evaluation of phage cocktail efficacy for controlling infections caused by pathogenic Escherichia coli in in vivo experiments - Alexyuk Madina; Alexyuk Pavel; Moldakhanov Yergali; Akanova Kuralai; Bogoyavlenskiy Andrey (BIO Web of Conferences, 2024)
Colibacillosis is a common veterinary infection that causes huge economic losses to the livestock and poultry industry. Uncontrolled use of antibiotics has led to the emergence and spread of multidrug resistant bacteria and has reduced the effectiveness of standard treatment regimens for infectious diseases. This stimulated the renewed interest in bacteriophages among scientists since the beginning of the 21st century. Bacteriophages are widespread in nature and accompany bacteria in every environment they colonize, including the microbiota of warm-blooded animals. The purpose of the research was to study the therapeutic activity of a cocktail created on the basis of bacteriophages isolated in the territory of the Republic of Kazakhstan. The therapeutic activity of the phage cocktail was determined through experimental infection of chickens with a pathogenic strain of E. coli. The in vivo experiments showed that the administration of the bacteriophage cocktail enabled 86% of the chickens to survive after being infected with lethal doses of pathogenic E. coli. They also revealed that the frequency of phage cocktail administration did not affect its efficacy. Thus, the investigated phage cocktail is a promising candidate for the creation of biotechnological antibacterial agents on its basis for safe and effective treatment of poultry against colibacillosis.